Forensic Linguistics of Extortion and Threats Among Young Couple via Social Media in Bengkalis - Eka Rahayu Putri; Hasnah Faizah; Muhammad Imam Arifandy; Nabilatuzzahwa Nabilatuzzahwa (Global Education : International Journal of Educational Sciences and Languages, 2025)
This research examines cases of extortion and threats between young couples through social media in Bengkalis. The analysis is conducted from the perspectives of forensic linguistics, semantics, and pragmatics. The research employs a qualitative approach with descriptive analysis. The data consists of language use in the Expert Witness Interview Report, specifically messages exchanged via WhatsApp. The findings indicate that the perpetrator engaged in both extortion and threats against the victim. The extortion involved financial demands, causing the victim to experience insecurity and trauma. Additionally, these actions violate Article 368, Paragraph 1 of the Criminal Code regarding extortion and threats against another person, as well as Article 45b of the Electronic Information and Transactions (ITE) Law, which addresses extortion and threats carried out online. Based on these findings, strict legal action is necessary, along with increased awareness of the importance of responsible social media use.